PENGARUH KEBIJAKAN DIVIDEN, PAJAK PENGHASILAN, DAN CASH HOLDING TERHADAP PRAKTIK PERATAAN LABA - NUR HIKMAH WIDYANINGSIH; Arya Pradipta; Dicky Supriatna (E-Jurnal Akuntansi TSM, 2022)
The purpose of this research is to determine whether dividend policy, income tax, cash holding, institutional ownership, net profit margin, and leverage affect the opportunities for income smoothing practice. This research data consists of manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2018-2020. This study used purposive sampling method and had a sample of 34 companies with a total of 102 companies. This study used binary logistic regression data processing. The results of the research obtained in this research are dividend policy, income tax, cash holdings, institutional ownership, net profit margins, and leverage have no influence on the practice of income smoothing